NILAI BUDAYA INDIGENOS, SUSTAINABLE DEVELOPMENT, DAN ERA INDUSTRI 4.0: PENGALAMAN PRIBADI DALAM PSIKOLOGI - Augustinus Supratiknya (PROSIDING SERINA, 2021)
Sustainable development as a continuation of the discourse of development that was designed by the developed nations for the underdeveloped ones during the Cold War era, has the potential of creating a dilemma between progress-welfare versus impoverishment-underdevelopment when confronted with the real situations of the poor-underdeveloped nations with their indigenous cultural values. The forthcoming of the Industry 4.0 era which is the cultural product of the developed nations seems to even accelerate the rate of underdevelopment of those poor-developing nations. Realizing the dilemma hidden in the discourse of development, Psychology with a cultural turn orientation gives more emphasis on the discourse of freedom-liberation as the goal of individual as well as social transformations. Hence, Psychology with a cultural turn orientation is basically open to any kinds of concepts and ideas as far as they are in line with or even strengthen its orientation towards the liberation of every person or groups of person for the creation of a common welfare which is truly just for all people Pembangunan berkelanjutan sebagai kelanjutan dari wacana pembangunan yang dirancang oleh bangsa-bangsa maju bagi bangsa-bangsa sedang berkembang dalam era Perang Dingin, tetap berpotensi menimbulkan dilema antara kemajuan-kesejahteraan versus pemiskinan-keterbelakangan jika dihadapkan dengan situasi nyata bangsa-bangsa miskin-terbelakang dengan nilai budaya indigenos mereka. Kehadiran era Industri 4.0 yang merupakan produk budaya bangsa-bangsa maju diduga justru berpotensi mempercepat laju keterbelakangan bangsa-bangsa miskin-sedang berkembang. Menyadari dilema yang tersembunyi dalam wacana pembangunan, Psikologi berorientasi hampiran budaya lebih mengutamakan wacana pembebasan-pemerdekaan sebagai tujuan transformasi individu maupun masyarakat. Untuk itu, Psikologi berorientasi hampiran budaya pada dasarnya terbuka terhadap semua konsep dan gagasan dari mana pun sepanjang sejalan atau bahkan memperkuat orientasinya ke arah pemerdekaan semua orang atau kelompok orang demi terciptanya kesejahteraan bersama yang sungguh-sungguh berkeadilan bagi semua orang.